TGF-β pathways in aging and immunity: lessons from Caenorhabditis elegans - Yamamoto, Katerina K.; Savage-Dunn, Cathy (Frontiers in Genetics, 2023)
The Transforming Growth Factor-β (TGF-β) superfamily of signaling molecules plays critical roles in development, differentiation, homeostasis, and disease. Due to the conservation of these ligands and their signaling pathways, genetic studies in invertebrate systems including the nematode Caenorhabditis elegans have been instrumental in identifying signaling mechanisms.C. elegans is also a premier organism for research in longevity and healthy aging. Here we summarize current knowledge on the roles of TGF-β signaling in aging and immunity.